2023
DOI: 10.3390/ijms24043963
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Heart Valves Will Displace Mechanical and Tissue Heart Valves: A New Era for the Medical Devices

Abstract: The development of a novel artificial heart valve with outstanding durability and safety has remained a challenge since the first mechanical heart valve entered the market 65 years ago. Recent progress in high-molecular compounds opened new horizons in overcoming major drawbacks of mechanical and tissue heart valves (dysfunction and failure, tissue degradation, calcification, high immunogenic potential, and high risk of thrombosis), providing new insights into the development of an ideal artificial heart valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 176 publications
0
11
0
Order By: Relevance
“…Silicone material and silicone liquids are widely used in clinical settings, including as heart valves, breast implants, retinal tamponades, and syringe barrel lubricants, [40][41][42][43][44] due to their versatility and relative biocompatibility. Recent findings have shown that when free silicone liquid is infused into silicone catheter materials, there is a remarkable decrease in both fibrinogen and pathogen adhesion levels, both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Silicone material and silicone liquids are widely used in clinical settings, including as heart valves, breast implants, retinal tamponades, and syringe barrel lubricants, [40][41][42][43][44] due to their versatility and relative biocompatibility. Recent findings have shown that when free silicone liquid is infused into silicone catheter materials, there is a remarkable decrease in both fibrinogen and pathogen adhesion levels, both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The polymeric leaflets have also better durability than pericardium leaflets. 1 Finally, the novel valve was implanted according to patient's wishes.…”
Section: Investigationsmentioning
confidence: 99%
“…Materials with good durability and biocompatibility have always been the research focus in the field of PHVs for many years. Polysiloxanes, polytetrafluoroethylene (PTFE) and polyurethane (PUs) are the earliest materials applied for developing PHVs, which have good biocompatibility, hemodynamic properties and viscoelasticity, respectively [ 4 , 5 ]. Still, as time goes on, many PHVs made from them have been tested and failed because of thrombosis, calcification, hydrolysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, no commercially−viable devices have been developed using macroscopic composite materials so far. Nanocomposites have a better application foreground because of their superior mechanical properties, biocompatibility and simpler valve manufacturing process [ 3 , 4 , 13 ], such materials include polyhedral oligomeric silsesquioxane poly(carbonate–urea) urethane (POSS−PCU), polyvinyl alcohol (PVA) hydrogels reinforced with bacterial cellulose (BC) [ 14 ], the integration of graphene oxide (FGO) nanomaterials and PCUs [ 15 ], and the addition of carbon nanotubes (CNTs) to polymers with acceptable biocompatibility and mechanical properties [ 16 , 17 ]. Except for POSS−PCU that has undergone in vitro testing [ 18 ], the other three nanocomposites are still in the early stages of development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation